COVID-19 and a Call to Adapt Dental Education - Alrashdi, Murad; Hameed, Ahmed; Aljabr, Abdullah (Frontiers in Dental Medicine, 2021)
Introduction: COVID-19 has harmed the economic, academic, and clinical pursuits of dental educational institutions and dental students. After dental associations, health agencies, and regulatory bodies around the globe announced the need for social distancing and for dental clinics to prioritize the safety and well-being of their staff, dental educational institutions worldwide have been burdened with figuring out how to adapt. Methods: This review attempts to provide a comprehensive picture of the initial response of dental schools worldwide to the COVID-19 crisis and determine what was informing their decisions at that particular time. An analytical approach was used to assess changes to dental school curriculums in didactic (academic/non-clinical) and clinical education, examinations, administration , and dental school research. The assessment was based on a comprehensive web-based search of a variety of online global references including research articles, reviews, letters, press releases, and surveys regarding the immediate effect of covid-19 on dental education at various dental institutions in the U.S, Europe, and Asia. The review also offered further recommendations to dental school administrators regarding the future of dental education during the pandemic. Conclusions: innovations in technology and educational methodologies will continue to influence how dental schools around the world adapt to the changes caused by COVID-19 and better prepare dental education institutions for potential future public health disruptions.